Irfan Abdul Hameed Fattah’s discourse on religious thought in response to the challenges of modernity - Abdul Rahim, Adibah (IIUM, 2018)
This paper will explore Irfan’s views on diversified philosophical trends which represent main qualitative characteristics of modernity. The author emphasizes the effort made by Irfan to answer what are the intellectual challenges of modernity posed by the West, and what are the major religious responses to modernity. A qualitative methodology in which the textual analysis and comparative study was employed to analyse textual materials related to the writings of Irfan and other figures. Findings indicate that the discussion on religious thought and the challenges of modernity is still relevant to contemporary time. It exerted impacts on the West particularly in Jewish and Christian religions, as well as the Muslim world. It led Irfan to take an initiative to deliberate it in an objective manner. Keyword: Irfan, Modernity, Islam, Christianity, Judaism, Religious thought.